Tree branch-shaped cupric oxide for highly effective photoelectrochemical water reduction. Issue 17 (18th March 2015) - Jang, Youn Jeong; Jang, Ji-Wook; Choi, Sun Hee; Kim, Jae Young; Kim, Ju Hun; Youn, Duck Hyun; Kim, Won Yong; Han, Suenghoon; Sung Lee, Jae
Abstract : The tree branch-shaped CuO, fabricated using the hybrid microwave annealing (HMA) process with a silicon susceptor shows excellent photoelectrochemical water reduction activity. Abstract : Highly efficient tree branch-shaped CuO photocathodes are fabricated using the hybrid microwave annealing process with a silicon susceptor within 10 minutes. The unique hierarchical, one-dimensional structure provides more facile charge transport, larger surface areas, and increased crystallinity and crystal ordering with less defects compared to irregular-shaped CuO prepared by conventional thermal annealing. As a result, the photocathode fabricated with the tree branch-shaped CuO produces an unprecedently high photocurrent density of −4.4 mA cm −2 at 0 VRHE under AM 1.5 G simulated sunlight compared to −1.44 mA cm −2 observed for a photocathode fabricated by thermal annealing. It is also confirmed that stoichiometric hydrogen and oxygen are produced from photoelectrochemical water splitting on the tree branch-shaped CuO photocathode and a platinum anode.